2016
DOI: 10.1007/s00198-016-3691-7
|View full text |Cite
|
Sign up to set email alerts
|

Strength measures are better than muscle mass measures in predicting health-related outcomes in older people: time to abandon the term sarcopenia?

Abstract: A simple lower limb strength assessment was at least as effective in predicting balance, functional mobility and falls in older people as more expensive and time-consuming muscle mass-based measures. These findings imply that functional terms such as muscle weakness or motor impairment are preferable to sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 55 publications
2
85
0
5
Order By: Relevance
“…It is in line with the existing literature reporting poor association between muscle mass‐based measures of sarcopenia and functional outcomes (i.e. mobility and disability) in the elderly . The present study utilized phase angle, an inspection technique of BIA, which is calculated directly without regression equation.…”
Section: Discussionsupporting
confidence: 62%
“…It is in line with the existing literature reporting poor association between muscle mass‐based measures of sarcopenia and functional outcomes (i.e. mobility and disability) in the elderly . The present study utilized phase angle, an inspection technique of BIA, which is calculated directly without regression equation.…”
Section: Discussionsupporting
confidence: 62%
“…Review of the titles and abstracts yielded 241 relevant studies for full‐text screening. Thirty‐six studies met all inclusion criteria and were included in this review . A total of 33 studies were included in the meta‐analysis; four of them presented data for both falls and fractures, leaving 20 studies included in the meta‐analysis for falls and 17 studies for fractures …”
Section: Resultsmentioning
confidence: 99%
“…Four studies included a combined group of hospitalized patients with fractures and community‐dwelling individuals without fractures . Two studies reported retrospective data, 20 studies were cross‐sectional, 13 studies were prospective, and 1 study was a randomized controlled trial examining the effect of nutritional supplementation on bone mineral density and risk of falls . Most of the studies were performed in Europe (12 studies), and Asia (12 studies), followed by Australia (5 studies), South America (4 studies), and North America (3 studies) .…”
Section: Resultsmentioning
confidence: 99%
“…The social domains of frailty might have greater impacts on muscle function and performance than on muscle mass. Muscle strength measures could be better than muscle mass parameters in predicting health‐related outcomes in older people . Results of the present study suggest that interventions to prevent social frailty might be particularly beneficial for community‐dwelling older adults for maintaining physical health.…”
Section: Discussionmentioning
confidence: 99%